(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the frequency of Irritable bowel syndrome (IBS) in patients presenting with abdominal pain. Study Design: Cross Sectional Study Place and Duration of Study: This study was conducted at the tertiary care teaching hospital attached to Al-Tibri Medical College, Isra University Campus, Malir Karachi from October 2021 to March 2022. Materials and Methods: Probability consecutive sampling technique was used. Data was collected from the patients diagnosed on basis of ROME –III criteria and were included in study. Data was analyzed by using SPSS version -25. Results: 130 patients who come to attended the gastroenterology out patient department with abdominal pain. Out of 130 patients 71were females and 59 were males. The age range of the total sample was 25-55 years. Age was classified into three groups 25 – 35years, 36-50 years and greater than 50 years. Mean age was 36.4 ±8.05 years. Frequency of Irritable Bowel Syndrome was matched with age, gender, smoking status, presence of diabetes and socio-economic/income status. Abdominal pain was relieved by defecation in 66.2%, change of stool frequency was found in 46.2% and change of stool form was found in 57.7%. The association of IBS with different study variables was done to check the effect modifiers by applying chi square test. Age group 25-35 years (p value 0.011) and female sex (p value 0.001) positively correlated with IBS as p value was found to be statistically significant. Conclusion: The prevalence of IBS in the female population is higher as compared in general population. This study also correlates IBS in patients who were smoker diabetics and also with variable socioeconomic status.